Структурні та оптичні характеристики композитів пірогенний кремнезем /a, b-Zn2SiO4:Mn - Oranska, O. I.; Bogatyrev, V. M.; Brichka, A. V.; Brichka, S. Ya.; Gornikov, Yu. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2015)
The structure, morphology, elemental composition, the fluorescent properties of the composites synthesized by surface modifying fumed silica with zinc and manganese acetate, followed by annealing in air at 930 and 1050°С, were studied by X-ray diffraction, scanning electron microscopy and optical spectroscopy. It is proved that the composites fumed SiO2 / α, β-Zn2SiO4: Mn, annealed at 1050° C exhibit fluorescence at wavelengths of 528 and 550 nm. Its intensity is defined by the modifications and perfection of the crystal structure of zinc acetate, depending on the method of applying metal acetates on the surface of SiO2, the content of Mn.